2009
DOI: 10.1101/sqb.2009.74.035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Mammalian Diversity

Abstract: Mammals have evolved a variety of morphological adaptations that have allowed them to compete in their natural environments. The developmental genetic basis of this morphological diversity remains largely unknown. Bats are mammals that have the unique ability of powered flight. We have examined the molecular embryology of bats and investigated the developmental genetic basis for their highly derived limbs used for flight. Initially, we developed an embryo staging system for a model chiropteran, Carollia perspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Comparative studies of gene expression during limb development indicate that there are several key genetic alterations that account for these differences. In the bat, upregulation of Prx1 results in a lengthening of the distal forelimb (Cretekos et al, 2008; Behringer et al, 2009; Figure 6A) and a posterior shift in Hoxd13 expression reduces some skeletal elements. In the mouse, BMPs trigger apoptosis of interdigit membranes.…”
Section: What Factors Contribute To These Changes?mentioning
confidence: 99%
“…Comparative studies of gene expression during limb development indicate that there are several key genetic alterations that account for these differences. In the bat, upregulation of Prx1 results in a lengthening of the distal forelimb (Cretekos et al, 2008; Behringer et al, 2009; Figure 6A) and a posterior shift in Hoxd13 expression reduces some skeletal elements. In the mouse, BMPs trigger apoptosis of interdigit membranes.…”
Section: What Factors Contribute To These Changes?mentioning
confidence: 99%
“…The family Vespertilionidae, which contains about one-third of all bat species and more than 100 species in the genus Myotis, ranks among the most species rich of all mammal families. Bats display many exceptional developmental and physiological characteristics, including the extreme elongation of digits to form webbed wings enabling powered flight, the capacity of several species to undergo extended hibernation, and extraordinary life spans for their size and metabolic rate (up to 34 years in the wild for Myotis), making them emerging models for research in limb development (2,3) and aging (4). Bats have also gained attention in biomedical research because a number of bat species have been identified as zoonotic reservoirs for some of the most sinister viruses infecting humans, such as rabies, Ebola, Marburg, Hendra, Nipah, and SARS-like viruses (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In contrast, PRX1 proteins shared 99% identity and no evidence suggested this protein differed in its activity between the two taxa 41. Finding that expression patterns, but not coding sequences, of these genes were unique in bats suggests that evolutionary modifications in regulatory regions are responsible for the unique phenotype of the bat wing 28…”
Section: Sequence Identity and Regulation Of Limb Patterning Genesmentioning
confidence: 99%
“…The developing forelimbs of bats display altered expression patterns of several genes (i.e., Fgf8 , HoxD, Prx1 ) known to pattern the limb relative to other studied tetrapods (e.g., mouse). However, analyses have indicated that the coding sequences of these differentially expressed genes are highly conserved in bats, humans, and mice 28,34,39,41. In bats, Fgf8 expression in the AER displays a dorsoventral expansion in width compared to mice,39 and during the fetal stages Fgf8 displays a novel expression domain in the interdigital tissues 8,12.…”
Section: Sequence Identity and Regulation Of Limb Patterning Genesmentioning
confidence: 99%
See 1 more Smart Citation